Antibiotic sensitivity patterns of Extended-Spectrum β-Lactamase urinary tract infections in Sri Lanka - Sebastiampillai, B.S.; Premaratna, B.A.H.R.; Luke, W.A.N.V.; Wickramasinghe, R.D.S.S.; Gunathilake, M.P.M.L.; Miththinda, J.K.N.D. (Faculty of Medicine, University of Kelaniya, Sri Lanka, 2016)
BACKGROUND: Extended-spectrum β-lactamase (ESBL) producing organisms causing urinary tract infections (UTI) are increasing in incidence and poses a major burden to health care requiring treatment with expensive antimicrobials and prolonged hospital stay. The prevalence of ESBL producing organisms particularly in the Asian region remains unknown. OBJECTIVES: To identify common ESBL producing organisms and to evaluate the antibiotic sensitivity patterns of ESBL UTIs in Sri Lanka. METHODS: Patients admitted with ESBL-UTI to Professorial Medical Unit, Colombo North Teaching Hospital, Ragama over a period of 6 months from January 2015 were recruited. Their Urine culture and ABST reports were analysed after obtaining informed written consent. RESULTS: Of the 52 patients who consented to be on the study, 30 (57.7%) were males. Mean age was 64.11 (SD=12.59) years. E. coli was the commonest organisms (84.6%; n=44), causing the ESBL-UTI followed by Klebsiella (15.4%; n=8). Fifty (96.2%) patients were sensitive to meropenem, 38 (73.1%) to imipenem, 30 (57.7%) to amikacin and 24 (46.2%) to nitrofurantoin. Meropenem resistance was found in 2 (3.8%) cases which were due to infection with E. coli.These two patients had received multiple antibiotics including meropenem in the recent past for recurrent UTI. CONCLUSIONS: While E. coli and Klebsiella are the commonest ESBL producing organisms causing UTI, carbapenems remain as the first line therapy. However 3.8% prevalence of meropenem resistance among the study population should draw attention of clinicians and needs implementation of measures to prevent emergence of carbapenum resistant ESBL organisms.
Free paper session 2: Infections OP 11 - 25th Anniversary International Scientific Conference, 6-8 April 2016, Faculty of Medicine,University of Kelaniya, Sri Lanka
Keywords: Antibiotic sensitivity